2002
DOI: 10.1093/oxrep/18.1.35
|View full text |Cite
|
Sign up to set email alerts
|

The Financing of Research and Development

Abstract: Evidence on the "funding gap" for R&D is surveyed. The focus is on financial market reasons for underinvestment in R&D that persist even in the absence of externality-induced underinvestment. The conclusions are that 1) small and new innovative firms experience high costs of capital that are only partly mitigated by the presence of venture capital; 2) evidence for high costs of R&D capital for large firms is mixed, although these firms do prefer internal funds for financing these investments; 3) there are limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
812
0
101

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,431 publications
(935 citation statements)
references
References 66 publications
22
812
0
101
Order By: Relevance
“…Financial barriers to innovation projects are closely related to some of their inherent characteristics (Hall, 2002) such as the low return expectation due to an inability to secure profits from an innovation, the higher cost of innovation projects, the high sunk costs, the specific dimension of the physical capital, the presence of externalities and free-riders, among others. All these characteristics reduce the capacity of financial institutions and financial markets to increase sources to firms' innovation projects.…”
Section: Financial Constraints and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial barriers to innovation projects are closely related to some of their inherent characteristics (Hall, 2002) such as the low return expectation due to an inability to secure profits from an innovation, the higher cost of innovation projects, the high sunk costs, the specific dimension of the physical capital, the presence of externalities and free-riders, among others. All these characteristics reduce the capacity of financial institutions and financial markets to increase sources to firms' innovation projects.…”
Section: Financial Constraints and Innovationmentioning
confidence: 99%
“…Furthermore, innovation projects show different characteristics in comparison with other projects. In particular, innovative firms encounter higher external financial difficulties to invest in new R&D projects, because their specific features increase risk and reinforce the informational problems with external investors (Hall, 2002). In fact, innovation is a complex process that frequently fails (Mazzucato, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Data would show a significant, although small, negative correlation between external and internal funding. The two channels of finance, indeed, are not expected to be unrelated, as servicing the debt reduces the cash flow for future investments (Hall, 1990;Hall, 2002;Czarnitzi & Hottenrott, 2011). Note.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Due to greater asymmetric information problems, SMEs mainly rely on internal finance which, indeed, enters at 1% level of significance. An extensive literature has observed that innovative firms face more severe external financial constraints (Hall & Lerner, 2010;Carpenter & Petersen, 2002b;Hall, 2002;Ughetto, 2008;Hall, 2002;Himmelberg & Petersen, 1994). Whenever possible, that is for sufficient levels of cash-flow, R&D expenditure is covered by internally generated funds, which are not affected by adverse selection problems.…”
Section: The Determinants Of Randd Expenditurementioning
confidence: 99%
See 1 more Smart Citation